Controlled synthesis of WO3 nanorods and their electrochromic properties in H2SO4 electrolyte - Wang, Jinmin (2012)
Uniform crystalline WO3 nanorods were synthesized by a lithium- or sulfate-free hydrothermal process with NaCl as a capping agent. It is found that variations in the pH and amount of capping agent have critical influence on the morphologies of the resultant WO3 nanostructures. The electrochromic film comprised of the as-synthesized crystalline WO3 nanorods exhibits a fast coloration/bleaching switching, coloration efficiency comparable to that of conventional amorphous WO3 films, and a high H+ ion-insertion ability in 0.5 mol/L H2SO4 solution without degradation.